El Amigo y El Esé: Stereotyping of the “Criminal Immigrant” - Caraballo, Krystlelynn (Criminal justice and behavior, 2023)
The criminal immigrant narrative (CIN) is the embodiment of stereotypes suggesting that foreign nationals are engaged in crime. Research has documented how this narrative has influenced discourse, policies, and enforcement, but none to date has addressed how the CIN affects the stereotyping and interactions of crime-involved individuals with those deemed “immigrants.” This study draws from in-depth, semi-structured interviews of 25 individuals actively engaged in street crime from Atlanta, Georgia, to understand their beliefs regarding immigration, stereotyping of “immigrants,” and their interactions with perceived immigrants, including targeting. Our findings suggest that interviewees’ stereotypes of immigrants and their ascribed attributes are based on perceived nationality, nativity, documentation status, work ethic, criminality, and prior interactions with foreign nationals. Participants demonstrated an understanding of immigration policies from media and political rhetoric. This understanding influenced the stereotyping of immigrants as “illegal” or “doing illegal things,” shaping participants’ views of foreign nationals as vulnerable or dangerous.